Analysis of Organizational Citizenship Behavior (OCB) Variables, Work Stress, Work Communication, Work Climate Affecting Employee Performance and Turnover Intention at PT. Bank Tabungan Negara (Persero) Tbk. Cabang Gresik - Hidayat, Wanda Gema P. A.; Tannady, Hendy (Publisher Cv. Inara, 2023)
This research attempts to illustrate and evaluate